Aesthetic aspects of plant communities of ruderal urban sites in Szczecin - Kazimierska, Natalia; Szymura, Magdalena; Wolski, Karol (Biodiversity: Research and Conservation, 2010)
Synanthropization of plant cover, connected with urban development, contributes to the appearance of specialized ruderal plant communities, adapted to habitats exposed to human influence. A lot of published data have focused on urban flora, but the aesthetic aspect of perennial and temporary plant communities at urban sites has been frequently omitted. Currently the practical use of such plant communities is limited by the lack of descriptive information available. In this study great attention has been paid to variability of urban communities, defined by: aesthetic aspects, flowering period, and colour variability in flowering communities. In Szczecin, Artemisio-Tanacetetum vulgaris, Calamagrostietum epigeji, Dauco-Picridetum hieracioidis, and Rudbeckio-Solidaginetum have been recognized as especially decorative. They could be used to reduce the costs of establishing and maintaining urban green areas.